Capabilities of the Canva web service for creating educational videos to improve the effectiveness of the educational process in flipped learning - Inna I. Kovtaniuk; Olena Yu. Tarasova; Iryna S. Zakarliuka (CTE Workshop Proceedings)
This paper examines the capabilities of the Canva web service for creating educational videos to enhance the effectiveness of flipped learning in higher education. The research addresses the challenges faced by Ukrainian educational institutions during times of crisis, including quarantine, war, and power outages, which have necessitated innovative approaches to education. Flipped learning, where students engage with instructional content independently before participating in interactive classroom activities, represents an increasingly significant pedagogical approach. The paper provides a comprehensive analysis of Canva's features for educational video creation, compares it with alternative tools, and offers step-by-step guidance for implementing Canva videos in Ukrainian educational contexts. Through detailed examination of technical integration with learning management systems, particularly Moodle, and consideration of best practices from international research, this paper presents practical strategies for educators. The findings suggest that Canva offers an accessible, versatile platform for creating engaging educational videos that can significantly enhance student engagement and learning outcomes in flipped learning environments, while addressing the specific challenges of the Ukrainian educational landscape.